2015
DOI: 10.1039/c5ce01585e
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved in situ studies on the formation mechanism of iron oxide nanoparticles using combined fast-XANES and SAXS

Abstract: The reaction of iron chlorides with an alkaline reagent is one of the most prominent methods for the synthesis of iron oxide nanoparticles. We studied the particle formation mechanism using triethanolamine as reactant and stabilizing agent. In situ fast-X-ray absorption near edge spectroscopy and small-angle X-ray scattering provide information on the oxidation state and the structural information at the same time. In situ data were complemented by ex situ transmission electron microscopy, wide-angle X-ray sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The acquired knowledge would facilitate the control of the formation of NPs in solution and tailor the properties of the final product. 41 In another publication, Leveneur et al investigated the nucleation and growth of Fe NPs in SiO 2 by TEM, XPS and XANES. It was demonstrated that ion implantation initially resulted in the formation of dilute cationic Fe 2+ species, while at higher dissolved iron concentrations, the formation of small metallic nuclei was noticed, which seed the nanocluster growth during prolonged implantation or annealing.…”
Section: X-ray-based Techniquesmentioning
confidence: 99%
“…The acquired knowledge would facilitate the control of the formation of NPs in solution and tailor the properties of the final product. 41 In another publication, Leveneur et al investigated the nucleation and growth of Fe NPs in SiO 2 by TEM, XPS and XANES. It was demonstrated that ion implantation initially resulted in the formation of dilute cationic Fe 2+ species, while at higher dissolved iron concentrations, the formation of small metallic nuclei was noticed, which seed the nanocluster growth during prolonged implantation or annealing.…”
Section: X-ray-based Techniquesmentioning
confidence: 99%
“…Recent examples utilised flow cells for small angle X-ray scattering (SAXS) and X-ray diffraction (XRD), mostly using synchrotron set-ups. [23][24][25][26][27] The in-line monitoring of the MNPs' magnetic properties during synthesis, however, has been reported with techniques not requiring special facilities. [28][29][30][31] Milosevic et al monitored the evolution of magnetic properties during a co-precipitation synthesis of iron oxide nano particles (IONPs) via the MIAtek® technology.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-phase products, forming for h 4 0.5 in iron aqueous solutions, have been exhaustively studied to explore structure, size, and morphology. 15,16,[18][19][20][21][22][23][24][25] Experimental methods applied include titration, UV-vis spectroscopy, 26,27 wide-and small-angle X-ray scattering (WAXS and SAXS), 19,28,29 X-ray absorption (XA) spectroscopy, 19,20,23,24,26,[29][30][31][32] and electron microscopy. 33 In the case of FeCl 3 aqueous solutions, the different experiments find that akaganeite (b-FeOOH) forms, for h 4 0.5.…”
Section: Introductionmentioning
confidence: 99%